2006
DOI: 10.1111/j.1439-0388.2006.00583.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characterisation and breed assignment in Austrian sheep breeds using microsatellite marker information

Abstract: Samples from 717 sheep of 11 Austrian sheep breeds were genotyped for 25 microsatellite loci. Twenty-one loci showing no deviation from Hardy-Weinberg equilibrium were used to calculate pairwise genetic distances (Nei's minimum distance and Reynolds' distance). All breeds could be clearly distinguished through these genetic distances. The shortest genetic distance was found between Alpines Steinschaf (AS) and Waldschaf (WS). Within the so-called 'Steinschaf' group [AS, Montafoner Steinschaf (MS), Krainer Stein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
50
7
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(78 citation statements)
references
References 21 publications
20
50
7
1
Order By: Relevance
“…Lack of differentiation between the Sicilian breeds could be due to geographic proximity, similarities in environment and breeding practices, but most likely due to past gene flow among them. These estimates of genetic differentiation are comparable to those reported by other authors for indigenous Ethiopian (F st = 0.046, Gizaw et al, 2007), Portuguese (F st = 0.049, Santos-Silva et al, 2008), and Alpine (F st = 0.057, Dalvit et al, 2008) sheep breeds and/or populations, but lower than those reported by Baumung et al (2006) in Austrian sheep breeds and Arora et al (2011) in Indian sheep breeds (0.080 and 0.111, respectively). Moreover, Lawson Handley et al (2007) in a study on European sheep breeds, including the COM and the SAR, reported that the Southern breeds are characterized by higher within-breed diversity, lower genetic differentiation, and higher level of heterozygosity than Northern breeds.…”
Section: Discussionsupporting
confidence: 76%
“…Lack of differentiation between the Sicilian breeds could be due to geographic proximity, similarities in environment and breeding practices, but most likely due to past gene flow among them. These estimates of genetic differentiation are comparable to those reported by other authors for indigenous Ethiopian (F st = 0.046, Gizaw et al, 2007), Portuguese (F st = 0.049, Santos-Silva et al, 2008), and Alpine (F st = 0.057, Dalvit et al, 2008) sheep breeds and/or populations, but lower than those reported by Baumung et al (2006) in Austrian sheep breeds and Arora et al (2011) in Indian sheep breeds (0.080 and 0.111, respectively). Moreover, Lawson Handley et al (2007) in a study on European sheep breeds, including the COM and the SAR, reported that the Southern breeds are characterized by higher within-breed diversity, lower genetic differentiation, and higher level of heterozygosity than Northern breeds.…”
Section: Discussionsupporting
confidence: 76%
“…To avoid bias because of unequal sample sizes, particularly for the Milchschaf breed, the bootstrapping method recommended by Simianer (2002) and Baumung et al (2006) was applied using 1000 samples with exactly 50 individuals per breed.…”
Section: Discussionmentioning
confidence: 99%
“…have used 25 microsatellites in 20 native and 12 imported North European sheep breeds in order to evaluate the importance of each breed for gene diversity. Baumung et al, (2006) have used 25 microsatellite markers for genetic characterization and breed assignment in 11 Austrian sheep breeds. Peter et al, (2007) have examined in a comprehensive study the genetic diversity of 57 European and Middle Eastern sheep breeds, using 31 microsatellites markers.…”
Section: Analysis Of Genetic Variation In Animalsmentioning
confidence: 99%
“…Microsatellites are used, in livestock species for estimating genetic variation within and among breeds (Buchanan et al, 1994;Cronin et al, 2009;Diez-Tascon et al, 2000a;Dowling et al, 2008;Schmid et al, 1999;Saitbekova et al, 1999), for admixture studies (Alvarez et al, 2004;Freeman et al, 2004Freeman et al, , 2006MacHugh et al, 1997;Vicente et al, 2008) and for assigning individuals to breeds (Baumung et al, 2006;Cornuet et al, 1999;Maudet et al, 2002;Meadows et al, 2006;Troy et al, 2001). …”
Section: Analysis Of Genetic Variation In Animalsmentioning
confidence: 99%